2001
DOI: 10.1176/jnp.13.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Psychosis Secondary to Traumatic Brain Injury

Abstract: Psychosis is a rare but devastating sequela of traumatic brain injury (TBI). This study examined risk factors for developing a psychosis secondary to TBI (PSTBI). Demographics of 25 inpatients with PSTBI were statistically analyzed for risk factors. Data from the PSTBI group were also compared with data from a control group of TBI patients without psychosis. Results indicate the PSTBI group was more likely to have had a previous congenital neurological disorder or to have sustained a head injury prior to adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…However, the role of TBI in the genesis of psychosis is a complex matter about which there is considerable scientific uncertainty and disagreement. Although the frequency of psychosis following TBI exceeds that of the general population (Davison & Bagley, 1969;Achte et al, 1969;Achte et al, 1991), there is often a considerable delay between TBI and the onset of psychotic symptoms (Fujii & Ahmed, 1996;Fujii & Ahmed, 2001;Sachdev et al, 2001). Once psychosis develops, the constellation of post-traumatic psychotic symptoms may be difficult to distinguish from those of schizophrenia , complicating the determination of the relationship, where such exists, between an often remote TBI and a recent-onset psychosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of TBI in the genesis of psychosis is a complex matter about which there is considerable scientific uncertainty and disagreement. Although the frequency of psychosis following TBI exceeds that of the general population (Davison & Bagley, 1969;Achte et al, 1969;Achte et al, 1991), there is often a considerable delay between TBI and the onset of psychotic symptoms (Fujii & Ahmed, 1996;Fujii & Ahmed, 2001;Sachdev et al, 2001). Once psychosis develops, the constellation of post-traumatic psychotic symptoms may be difficult to distinguish from those of schizophrenia , complicating the determination of the relationship, where such exists, between an often remote TBI and a recent-onset psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…The post-traumatic psychoses are often 'atypical' with regard to age of onset (Fujii & Ahmed, 2001;Sachdev et al, 2001;Fujii & Ahmed, 2002), symptom types (Goethe & Levin, 1984), neuroimaging findings (Fujii & Ahmed, 2002), and the presence of comorbid conditions such as epilepsy (Hillbom, 1960;Fujii & Ahmed, 1996) and/or associated cognitive impairment (Fujii & Ahmed, 2002) when compared to the primary psychotic disorders. These differences between psychosis due to TBI and the primary psychotic disorders suggest that TBI may be more than a risk factor for the development of the primary psychotic disorders; it may in some cases be an etiology of psychosis in its own right.…”
Section: Introductionmentioning
confidence: 99%
“…11 Persons with risk factors for developing a psychosis secondary to TBI are more likely to have had a previous congenital neurological disorder or to have sustained a head injury prior to adolescence. 12 Lifetime incidence rates of TBI survivors who later demonstrate psychotic symptoms vary across studies, varying from 3.4% to 8.9%. 13,14 The onset of psychosis after TBI is highly variable but is generally delayed.…”
mentioning
confidence: 99%
“…In their study of World War II veterans, Achte et al 15 reported that the occurrence of psychotic symptoms ranged from 2 days to 48 years after injury, with 42% experiencing their first psychotic episode 10 or more years after sustaining a missile wound to the head. Fujii and Ahmed 16 reported a range from 3 months to 19 years, with a mean onset of 5.9 years after closed head trauma. Feinstein and Ron 17 reported a mean latency of 11.7 years, with a range of 0 to 52 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation